An assessment of the administrative capability of local governments in the National Capital Region in implementing the gender mainstreaming policy - Sarmiento, La Rainne Abad (2005)
The research examines the extent of the administrative capability to implement the Gender and Development (GAD) mainstreaming policy by local government units (LGUs) in the National Capital Region (NCR). It surveyed strategies to improve the policy implementation approaches through case studies that highlighted the experience in GAD mainstreaming in Las Piñas City